Konsep Konservasi Sumber Air Dilem bagi Kebutuhan Masyarakat Lingkungan Papring Kecamatan Kalipuro Kabupaten Banyuwangi - Gatut Rubiono; Anas Mukhtar (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Conservation of water sources is very necessary for the needs of daily life. Community service cleaning and identification of the Dilem water source area in the Papring Neighbourhood has been carried out by the Mechanical Engineering Student Association of PGRI Banyuwangi University. The purpose of this article is to develop the concept of water source conservation for the needs of the Papring Village community, Kalipuro Sub-district, Banyuwangi District. The concept is prepared based on information and data that has been obtained from the surrounding community and from the implementation of cleaning activity of the water source area. A simple schema of the source area is made as the basis for drafting the concept. The concept of conservation is structured in the form of steps or methods that may be applied in the source area.